Proceso de atención de enfermería en neonato pretérmino tardío con insuficiencia respiratoria. - Orellana Bravo, Karla Stefania (2020)
A most commonly observed alteration in preterm neonates is respiratory failure, known as respiratory deficiency syndrome, so it is common to observe such alterations in most cases admitted to a neonatal intensive care room.. The incidence of respiratory deficiency in premature neonates has progressively decreased since the 1990s, and despite this, between 10.5 and 0.3% of newborns between 34 and 37 weeks of gestation have respiratory deficiency syndrome, at a lower gestational age, the greater the risk of developing complications. As a highly complex alteration, clinical care should be prioritized and strict monitoring of the respiratory development of the newborn will be carried out. Respiratory deficiency in the preterm newborn is due to the pulmonary surfactant deficiency that fulfills the role of tensoactive substance, i.e. it will decrease surface tension and help maintain the stability of the alveoli during the breathing process. Because of this deficit there is a respiratory syntometological picture that can compromise the life of the preterm newborn. The objective of this case study is to determine the nursing care process in a late preterm newborn with respiratory deficiency, to help correct the functional patterns that are affected and thus choose the appropriate nursing interventions in order to facilitate the reduction of possible complications and ensure early recovery of the newborn.